Selected determinants and directions of the new way of thinking in economic sciences - Banaszyk, Piotr; Deszczyński, Przemysław; Gorynia, Marian; Malaga, Krzysztof (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2023)
The text is devoted to new trends and changes emerging in the economic sciences, focused on growth, socio-economic development and income inequalities in the context of the idea of global rationality, understood as the ability to sustain the long-term existence of civilization on the entire planet. The thematic scope of this problem is broad; thus it is impossible to cover all its complexity in one study. Hence, attention is focused on selected aspects of the issues raised: on issues related to growth and development as well as economic inequalities, the economic foundations of growth, and the issue of substituting natural capital by human capital. A critical diagnosis and postulates for the future, with regard to measures of well-being in the context of the idea of sustainable development, are also considered as well as including the issue of sustainable development in development economics. The article ends with concluding remarks highlighting the thesis that economic growth should now be acceptable only when it does not excessively exploit natural capital and does contribute to deteriorating the quality of life. As for the methodological side of the text, it was created mainly through analysing the literature on the subject, but attention should be paid to the original nature of some predictions and recommendations, which were made as a result of the assumptions of the so-called diagnostic and prognostic analysis.